1989
DOI: 10.1007/bf00274530
|View full text |Cite
|
Sign up to set email alerts
|

A single major gene controls most of the difference in susceptibility to streptozotocin-induced diabetes between C57BL/6J and C3H/HeJ mice

Abstract: To assess genetic factors determining sensitivity to streptozotocin-induced diabetes in inbred strains of mice, a genetic analysis of streptozotocin-sensitive C57BL/6J and streptozotocin-resistant C3H/HeJ mice was performed. One week after a single dose of streptozotocin (200 mg/kg body weight), differences in plasma glucose concentration were marked between male mice of the C57BL/6J and C3H/HeJ strains (p less than 0.001). To determine the number of genes responsible for the difference, F1 male progeny of a c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
1

Year Published

1996
1996
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 30 publications
0
7
1
Order By: Relevance
“…Indeed, in contrast to a previous study which claimed that a single major gene controlled the difference in susceptibility to HDS-diabetes between C57BL/6 J and C3H/Hej [18], our work indicates that NOD susceptibility to HDS-diabetes is controlled by many genes, only two of which were detected by our genome scan.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Indeed, in contrast to a previous study which claimed that a single major gene controlled the difference in susceptibility to HDS-diabetes between C57BL/6 J and C3H/Hej [18], our work indicates that NOD susceptibility to HDS-diabetes is controlled by many genes, only two of which were detected by our genome scan.…”
Section: Discussioncontrasting
confidence: 99%
“…Moreover, we expected that the genetics of the susceptibility of the NOD mouse to toxic HDS-diabetes would be less complex than that of the spontaneous disease. A previous study suggested that a single major gene could determine the susceptibility of C57BL/6 mouse to HDS-diabetes [18].…”
mentioning
confidence: 99%
“…A single high dose of STZ (80 -200 mg/kg) is thought to produce a combination of apoptosis and necrotic damage of ␤ cells (30,31). Interestingly, a role for an immune response in the single high dose of STZ model is suggested from studies using TLR4-deficient C3H mice (32) and those demonstrating activation of islet Ag-specific T cells in PDLN after a single STZ dosing (11,31,33,34).…”
Section: Elevated Expression Of Hsc70 Increases Diabetes Following Ismentioning
confidence: 99%
“…Our results in this study showed that B6 demonstrated relatively low GHR mRNA levels in liver, but the opposite trend was observed in skeletal muscle. The relatively increased GH action in skeletal muscle may be one of the explanations for the susceptibility to the development of diabetes in B6 compared with C3H (Kaku et al 1989). Normal GHR and IGF-I receptor signaling in skeletal muscle may also explain the normal growth in B6 compared with C3H.…”
Section: Figurementioning
confidence: 99%
“…C3H mice with higher serum IGF-I levels have increased BMD compared with B6. B6 mice have higher glycosylated hemoglobin levels (Kaku et al 1989) and demonstrated poor glucose tolerance with a lower insulin response to i.p. glucose administration compared with C3H (Kayo et al 2000).…”
Section: Introductionmentioning
confidence: 99%